2019
DOI: 10.1371/journal.pone.0221634
|View full text |Cite
|
Sign up to set email alerts
|

Comparative multi-omics systems analysis reveal the glycolysis / gluconeogenesis signal pathway play an important role in virulence attenuation in fish-derived GBS YM001

Abstract: Streptococcus agalactiae (GBS) is a seriously threat to the farmed tilapia, and oral vaccination was considered to be the most desirable means which requires deep understanding of virulence mechanism of the fish-derived GBS. Our previous genome study of the fish-derived attenuated strain YM001 showed that there were two large deletions in YM001 compared to its parental virulent strain HN016. In this study, a combined transcriptomic and proteomic analysis was performed on YM001 and HN016 strains, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…RNA-seq provides a sensitive method for global gene expression analysis in infection biology [21]. Previous combined transcriptomic and proteomic studies on HN016 and its attenuated strain YM001 cultured in vitro have shown that the pentose phosphate pathway and pyruvate metabolism pathway that affecting the growth of the strain may be one of the important reasons for the virulence attenuation in HN016 [28]. However, as bacterial infections of eucaryon involve two interacting organisms, there are interactions between the bacteria and the host.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq provides a sensitive method for global gene expression analysis in infection biology [21]. Previous combined transcriptomic and proteomic studies on HN016 and its attenuated strain YM001 cultured in vitro have shown that the pentose phosphate pathway and pyruvate metabolism pathway that affecting the growth of the strain may be one of the important reasons for the virulence attenuation in HN016 [28]. However, as bacterial infections of eucaryon involve two interacting organisms, there are interactions between the bacteria and the host.…”
Section: Discussionmentioning
confidence: 99%
“…Refer to our previous study [29], the cultured strains were stored in TRizol and transported with liquid nitrogen. RNA sequencing was performed by Novogene Co, LTD (Beijing, China).…”
Section: Rna-sequencingmentioning
confidence: 99%